1997
DOI: 10.1177/096120339700600105
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus: clinical expression and anti-Ro/SS—A response in patients with and without lesions of subacute cutaneous lupus erythematosus

Abstract: The presence of SCLE lesions in patients with SLE is associated with a more favourable prognosis. The major anti-Ro/SS-A response is directed against the native 60 kD Ro/SS-A protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
1
17
0
7
Order By: Relevance
“…There is little evidence that anti-ENA specificity or titres reflect SLE activity, 68 73 but anti-Ro is associated with cutaneous involvement in subacute cutaneous lupus erythematosus, 74 and with congenital heart block (CHB). 75 Anti-Ro52 in isolation is associated with CHB but is not detected by assays containing only Ro-60, 76 such as HEp-2000 cells.…”
Section: Monitoringmentioning
confidence: 99%
“…There is little evidence that anti-ENA specificity or titres reflect SLE activity, 68 73 but anti-Ro is associated with cutaneous involvement in subacute cutaneous lupus erythematosus, 74 and with congenital heart block (CHB). 75 Anti-Ro52 in isolation is associated with CHB but is not detected by assays containing only Ro-60, 76 such as HEp-2000 cells.…”
Section: Monitoringmentioning
confidence: 99%
“…The diagnosis of SLE was based on fulfillment of 4 or more of the ACR criteria. 6 Clinical and laboratory data were obtained from reviews of medical records from the practices. Medical records were also obtained from each patient's primary care physician, nephrologist, hematologist, and neurologist, when applicable.…”
Section: Methodsmentioning
confidence: 99%
“…We did not exclude patients with SCLE who fulfilled the ACR diagnostic criteria for SLE. 6 Control subjects were selected from patients with SLE who were followed up by physicians at Rheumatology Associates, Louisville. Patients with SLE consenting to participate in our research project were matched by age (±2 years), sex, and ethnicity with at least 1 of our patients with SCLE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies comparing patients with SCLE versus those with only SLE have demonstrated that patients with SCLE are less likely to have severe renal and central nervous system disease, suggesting that SCLE differs from SLE by involving less internal organ disease [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%